NPEGL Old Swedish - Språkbanken Text (University of Gothenburg, 2024)
The Old Swedish part of the database developed in the context of Constraints on syntactic variation: Noun phrases in early Germanic languages.

Den fornsvenska delen av databasen till projektet Constraints on syntactic variation: Noun phrases in early Germanic languages.
NPEGL Fornsvenska
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik